The Use of Visual Media in History Learning to Increase the Creativity of X E 11 Students at SMA Negeri 3 Purwokerto - Rahmasari, Atiqah (Mitreka Satata: Journal of Historical Studies and History Education, 2025)
In 21st century learning, students are too spoiled by technology so that students' creativity in developing their ideas tends to decrease. Apart from that, students previously experienced online learning for approximately 2 years during the Covid-19 pandemic so that students' habits during online learning are still carried over to now. Teachers also need to learn to develop the learning media used so that it doesn't seem monotonous in learning. Actions that can be taken in an effort to increase students' creativity are utilizing visual media to train students' creativity. Visual media that can be used are infographics and comics. The research subjects in this study were students in class X E 11 of SMA Negeri 3 Purwokerto for the 2023/2024 academic year. Data collection techniques use observation and the results of calculating scores from students' work. The data analysis technique in this study used the Wilcoxon test to find differences between the results of actions in the pre-cycle, cycle 1 and cycle 2. The results showed an increase from the pre-cycle to cycle one and cycle two. The highest creativity results were in cycle 2 using visual media in the form of comics. This proves that visual media can increase students' creativity.